Initial Public-Health Emergency Response to SARS and COVID-19 Pandemics in Mainland China: A Retrospective Comparative Study - Zhu H; Wang Q; Zhang T; Liu X; Dai R; Wu P; Bai G; Wang Y; Zhou P; Luo L (Dove Medical Press, 2021)
Huanhuan Zhu,1 Qian Wang,1 Tiantian Zhang,2,3 Xin Liu,1 Ruiming Dai,4 Ping Wu,1 Ge Bai,1 Ying Wang,1 Ping Zhou,1 Li Luo1,3,5 1School of Public Health, Fudan University, Shanghai, 200032, People's Republic of China; 2School of Social Development and Public Policy, Fudan University, Shanghai, 201203, People's Republic of China; 3Key Laboratory of Public Health Safety of the Ministry of Education and Key Laboratory of Health Technology Assessment of the Ministry of Health, Fudan University, Shanghai, 200032, People's Republic of China; 4Department of Scientific Research, Fudan University Shanghai Cancer Center, Shanghai, 200032, People's Republic of China; 5Shanghai Institute of Infectious Disease and Biosecurity, School of Public Health, Fudan University, Shanghai, 200032, People's Republic of ChinaCorrespondence: Li LuoFudan University, 130 Dong'an Road, Xuhui District, Shanghai, 200032, People's Republic of ChinaEmail liluo@fudan.edu.cnBackground: Severe acute respiratory syndrome (SARS) was reported first in China in 2003. The world is currently coping with coronavirus disease-2019 (COVID-19). We conducted a retrospective study to compare the initial public-health emergency response (PHER) to SARS and COVID-19 in mainland China.Methods: A qualitative comparative study was conducted to compare the PHER timelines to SARS and COVID-19 by selecting six crucial time points. Besides, we explored the speed of spread, peak time and plateau period of SARS and COVID-19, respectively, by comparing the confirmed cases in the same time interval.Results: The government of the People's Republic of China (PRC) accomplished the entire initial PHER to SARS in 127 days and for COVID-19 in 44 days. The speed of PHER for COVID-19 was 83 days faster. The peak time of SARS arose ∼ 80 days later than that of COVID-19. Though the peak number of confirmed daily cases for COVID-19 was fivefold more than that of SARS, the onset of the stabilization period for COVID-19 was > 2 months earlier than that of SARS.Conclusion: Overall, the speed of the initial PHER to COVID-19 pandemic was faster than that for SARS. Compared with the speed of hospital reporting and government policymaking, the speed of pathogen identification improved the most. The COVID-19 pandemic curve entered a plateau period earlier than the SARS pandemic curve, which suggests that the pandemic was controlled more effectively because of a timely PHER. The PRC government should emphasize improving the ability of hospitals to restrain infectious diseases by enhancing the direct reporting system and cultivating crisis management to empower relevant individuals to make timely scientific decisions.Keywords: severe acute respiratory syndrome, SARS, coronavirus disease-2019, COVID-19, infectious diseases, public health, emergency response